The Law of the Sea: A Select Bibliography 2013 - United Nations Office of Legal Affairs (United Nations, 2019)
Compiled by the United Nations Office of Legal Affairs, this bibliography covers 20 subject categories based on the major topics of the United Nations Convention of the Law of the Sea. It is intended for the use of those interested in ocean affairs and the law of the sea matters in general and in the UN Convention on the Law in the Sea.